Biocompatibility and antibacterial behavior of electrochemically deposited Hydroxyapatite/ZnO porous nanocomposite on NiTi biomedical alloy. Issue 11 (1st June 2022) - Mehrvarz, Alireza; Khalil-Allafi, Jafar; Khosrowshahi, Amir Kahaie
Abstract: In this article, Hydroxyapatite (HA) and its composite with ZnO nanoparticles were electrochemically deposited on NiTi superelastic alloy to evaluate the effect of nanoparticles on its various properties. Morphological observations revealed that the addition of 400 mg/L ZnO nanoparticles created an HA layer with a porous network structure. FTIR and GIXRD results pointed out that the nanoparticles contributed to pure HA synthesis. Given AFM topography parameters, a significant rise was detected in roughness values as ZnO entered the HA matrix. The rough surface with a larger volume of porosity improved the wettability of the composite coating by reducing the contact angle to approximately half of its initial value (14.57°). Furthermore, ZnO incorporation proved to be quite helpful in contact with living species. Cell culture assessments disclosed the considerable impact of ZnO nanoparticles on MG-63 osteoblast-like cells' attachment and proliferation on the composite coating. They also improved cell viability reported by the MTT assay. The antibacterial resistance of HA and HA/ZnO coatings was investigated against E. Coli and S. Aureus bacteria colonies by the disk diffusion method. For the first time, the pure HA matrix showed antibacterial activity, though insignificant. The addition of ZnO nanoparticles promoted this behavior which was more vigorous in the case of S. Aureus bacteria.